Effect of the maternal childbirth experience on a subsequent birth: A retrospective 7-year cohort study of primiparas in Finland - Joensuu Johanna M.; Saarijärvi Hannu; Rouhe Hanna; Gissler Mika; Ulander Veli-Matti; Heinonen Seppo; Torkki Paulus; Mikkola Tomi (BMJ Publishing Group, 2025)
Objective To study the effect of the childbirth experience on the likelihood and interval to a subsequent live birth.
Design Retrospective analysis of a 7-year cohort.
Setting Childbirths in Helsinki University Hospital delivery units.
Participants All parturients giving birth to a term and living baby from a single pregnancy in Helsinki University Hospital delivery units from January 2012 to December 2018 (n=120 437). Parturients delivering their first child (n=45 947) were followed until the birth of a subsequent child or the end of 2018.
Main outcome measure The interval to a subsequent childbirth connected to the experience of the first childbirth was the primary outcome of the study.
Results A negative first childbirth experience decreases the likelihood of delivering a subsequent child during the follow-up (adjusted HR=0.81, 95% CI 0.76 to 0.86) compared with those experiencing the first childbirth as positive. For parturients with a positive childbirth experience, the median interval to a subsequent delivery was 3.90 years (3.84–3.97) compared with 5.29 years (4.86–5.97) after a negative childbirth experience.
Conclusion The negative childbirth experience influences reproductive decisions. Consequently, more focus should be placed on understanding and managing the antecedents of positive/negative childbirth experiences.